H-Phosphonate Chemistry in the Synthesis of Electrically Neutral and Charged Antiviral and Anticancer Pronucleotides - Kraszewski, Adam; Sobkowski, Michal; Stawinski, Jacek (Frontiers in Chemistry, 2020)
In this review a short account of our work on synthesis and biological activity of electrically neutral and charged anti-HIV and anticancer pronucleotides, presented on the background of the contemporary research in this area, is given